Measuring the quantum state of photoelectrons - Laurell, Hugo; Busto, David (Lund University, 2024)
The dataset contains the continuous-variable quantum state tomography protocol for photoelectrons (KRAKEN) scans for helium and argon. KRAKEN is a protocol that enables tomography of photoelectrons by reconstructing their density matrix. The dataset also includes data for the photoelectron spectrometer's response function and IR spectra.

Datamängden innehåller det kontinuerliga variabelkvanttillståndstomografiprotokollet för fotoelektroner (KRAKEN) skanningar för helium och argon. KRAKEN är ett protokoll som möjliggör tomografi av fotoelektroner genom att rekonstruera deras densitetsmatris. Datasetet innehåller även data för fotoelektronspektrometerns responsfunktion och IR-spektra.
Mätning av fotoelektroners kvanttillstånd
Keywords: quantum mechanics; kvantmekanik; quantum entanglement; kvantsammanflätning; photoelectron spectroscopy; photoelectrons; Atom and Molecular Physics and Optics; Atom- och molekylfysik och optik